Human Commensal Prevotella histicola Ameliorates Disease as Effectively as Interferon-Beta in the Experimental Autoimmune Encephalomyelitis - Shahi, Shailesh K.; Jensen, Samantha N.; Murra, Alexandra C.; Tang, Na; Guo, Hui; Gibson-Corley, Katherine N.; Zhang, Jian; Karandikar, Nitin J.; Murray, Joseph A.; Mangalam, Ashutosh K. (Frontiers in Immunology, 2020)
Gut microbiota has emerged as an important environmental factor in the pathobiology of multiple sclerosis (MS), an inflammatory demyelinating disease of the central nervous system (CNS). Both genetic and environmental factors have been shown to play an important role in MS. Among genetic factors, the human leukocyte antigen (HLA) class II allele such as HLA-DR2, DR3, DR4, DQ6, and DQ8 show the association with the MS. We have previously used transgenic mice expressing MS susceptible HLA class II allele such as HLA-DR2, DR3, DQ6, and DQ8 to validate significance of HLA alleles in MS. Although environmental factors contribute to 2/3 of MS risk, less is known about them. Gut microbiota is emerging as an imporatnt environmental factor in MS pathogenesis. We and others have shown that MS patients have distinct gut microbiota compared to healthy control (HC) with a lower abundance of Prevotella. Additionally, the abundance of Prevotella increased in patients receiving disease-modifying therapies (DMTs) such as Copaxone and/or Interferon-beta (IFNβ). We have previously identified a specific strain of Prevotella (Prevotella histicola), which can suppress experimental autoimmune encephalomyelitis (EAE) disease in HLA-DR3.DQ8 transgenic mice. Since Interferon-β-1b [IFNβ (Betaseron)] is a major DMTs used in MS patients, we hypothesized that treatment with the combination of P. histicola and IFNβ would have an additive effect on the disease suppression. We observed that treatment with P. histicola suppressed disease as effectively as IFNβ. Surprisingly, the combination of P. histicola and IFNβ was not more effective than either treatment alone. P. histicola alone or in combination with IFNβ increased the frequency and number of CD4+FoxP3+ regulatory T cells in the gut-associated lymphoid tissue (GALT). Treatment with P. histicola alone, IFNβ alone, and in the combination decreased frequency of pro-inflammatory IFN-γ and IL17-producing CD4+ T cells in the CNS. Additionally, P. histicola alone or IFNβ alone or the combination treatments decreased CNS pathology, characterized by reduced microglia and astrocytic activation. In conclusion, our study indicates that the human gut commensal P. histicola can suppress disease as effectively as commonly used MS drug IFNβ and may provide an alternative treatment option for MS patients.